The Impact of Modified Atmosphere Storage Treatment on Glucose Levels and Mass Transfer Coefficients: A Study Based on Fruit Skin Thickness - Agri Suwandi; Wina Libyawati; Esti Mulatsari (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2024)
Modified atmosphere storage (MAS) has been proven for decades able to decelerate the respirate rate of fruits. The sluggish respirate rate increases the shelf life of fruits. The after-effects of MAS treatment have been investigated from the installation design until gas composition in the storage, however the investigation about the correlation between the treatment level and the fruits characteristic is still limited on the flavor, color, and weight. Therefore, the research goal is to investigate the MAS treatment result based on skin thickness. A series of experiments with full factorial arrangement and three replications, is set in a storage installation. Skin thickness is classified in to three levels, which are thin, medium, and thick. Each level is represented respectively by orange, banana, and watermelon. Both fruits with and without MAS treatment are quantified by measuring glucose level, to make a comparation. The outcome of the research from measurement shows fruits which undergo MAS treatment have lower glucose levels than the ones without the treatment, but the weight remains the same. The mass transfer coefficient with the thickness became a baseline for sudden exchange in the storage.